2010
DOI: 10.12927/hcpol.2013.21740
|View full text |Cite
|
Sign up to set email alerts
|

Anthropological Approach to Adherence Factors for Antihypertensive Drug Therapy

Abstract: Objective: uncontrolled high blood pressure leads clinicians to wonder about adherence degree among hypertensive patients. In this context, our study aims to describe and analyze patients' experience of antihypertensive drugs in order to shed light on the multiple social and symbolic logics, forming part of the cultural factors shaping personal medication practices. Methods: The medical inductive and comprehensive anthropological approach implemented is based on an ethnographic survey (observations of consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In many studies, non-compliance with antihypertensive therapy was responsible for two-thirds of the cases of uncontrolled hypertension 33,34. Krousel-Woods et al33 found that non-compliance was associated with a nearly two-fold greater risk (OR 1.68; 95% CI 1.01–2.88) of uncontrolled BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, non-compliance with antihypertensive therapy was responsible for two-thirds of the cases of uncontrolled hypertension 33,34. Krousel-Woods et al33 found that non-compliance was associated with a nearly two-fold greater risk (OR 1.68; 95% CI 1.01–2.88) of uncontrolled BP.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, non-compliance with antihypertensive therapy was responsible for two-thirds of the cases of uncontrolled hypertension. 33 , 34 Krousel-Woods et al33 found that non-compliance was associated with a nearly two-fold greater risk (OR 1.68; 95% CI 1.01–2.88) of uncontrolled BP. Yaméogo et al25 in Burkina Faso found that non-compliance with both diet and antihypertensive therapy was associated with an eightfold (OR 8.40; 95% CI 1.11–4.17; p = 0.04) and nearly three-fold greater risk of uncontrolled hypertension, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of HBPM has to be accompanied by professional, and be performed rigorously for a better adherence and so a better control of hypertension. Adherence is influenced by sociocultural and psycho-behavioral factors specific to patients, and the quality of the doctor-patient relationship [29,30]. It is likely that participants in our survey who used the HBPM correctly received better information from their GP, thus developing self-care competencies [31].…”
Section: Comparison With Literaturementioning
confidence: 99%
“…More generally, the attraction and even loyalty and closeness sometimes felt to a drug [ 29 ] may rest in part on the name. Brand loyalty in general is central to marketing, although ultimately, in the words of Rotfeld [ 62 ], ‘so little is known about how or why advertising works’.…”
Section: Do Drug Names Carry Meaning?mentioning
confidence: 99%
“…Or, more likely, there is an interaction of sorts going on, part of what Halliday [ 15 ] terms a social semiotic but constantly morphing as the interaction progresses. By contrast, adherence to a medicine has been found expressed in terms of fear (the invisible disease), self-preservation (‘taking care of oneself’), and variations on a theme of trust: trust in the drug and trust in one’s physician [ 29 ].…”
Section: Introduction: Key Conceptsmentioning
confidence: 99%